Aplikasi Penjadwalan Asisten Penjaga Ujian dengan Metode Algoritma Genetika - Joseph Clinton Adi Gunawan Putra; Kristo Radion Purba; Henry Novianus Palit (Jurnal Infra, 2016)
At the time ahead of midterm or in semester’s final exam at Petra Christian University is definitely needed assistants that will keep on every class on the test subjects. Therefore we need a proctor before determining a schedule that will be covered, it would require a meeting in order to determine the schedule. So this application is made to be easier for assistants and coordinator of exam to determine the schedule and not waste more time between coordinator. The coordinator and assistant simply open the application. The assistant can put their schedule in accordance with the date and time of their examinations, and the coordinator can also produce the program by using genetic algorithm with the restrictions that have been given by the exam’s coordinator. So the schedule that has been produced have a match with the end result. And has a variety of additional features such as providing notice to assistant, and export schedules make it to Microsoft Office Excel or print directly. At the time of the survey the genetic algorithm, this program has a schedule in accordance with the limit given by the coordinator of the exam. So this program should be used by the coordinator of the exam of Petra Christian University in the study program information technology.